Juridical Study in The Application of the Law About Foster- Child Adoption in Indonesia by Foreign Nationals - Bernadeta Resti Nurhayati; Ignatius Hartyo Purwanto (Media Komunikasi FPIPS, 2021)
The adoption or adopting transfer of rights to child from authority of parents, legal guardians, or other people who responsible for nurturing, educating, and raise the child to his foster parents family based on law or sentence. Adoption might be conducted to Indonesian children by parents of Indonesian or even in some special cases, adoption can be conducted by foreign nationals. The adoption of Indonesian children by foreign nationals is restricted. This is due to the protection of foster-children who adopted by foreign nationals, so that they do not experience unwanted things considering that the child will be taken abroad by the foster parents. Incidents such as children who, after being taken by their foster parents, experience violence or become victims of human trafficking are things that must be considered before deciding to allow the adoption of Indonesian children by foreign nationals.